Variations in Morphometric Traits of Muscovy Ducks Measured at PNGUNRE Poultry Farm - Lan , Limai; Worowan, Leonie (International Journal of Poultry Science, 2021)
Background and Objectives: Morphometric traits play important role in the selection and breeding programs for genetic improvement of Muscovy ducks. The objective of the current study was to measure variations in some morphometric traits using the plumage colors of Muscovy duck population under farm conditions. Materials and Methods: This study was conducted at the poultry unit of PNG-UNRE farm using 38 randomly mated adult Muscovy ducks. Four phenotypes (plumage colors); [Chocolate (n = 7), Lavender, (n = 5), Silver (n = 7) and White (n = 19)] were measured. Copra meal was fed to birds daily and allowed to scavenge during the day within the fenced farm. Means and standard deviations of all measured traits were computed. Results: White phenotype was dominant among Muscovy duck population under farm conditions. The highest body weight (BW = 1875.71±243.64 g) and body size (BS = 30.86±1.57 cm) was observed in silver colour. The highest shank length (SL = 4.86±0,69 cm), body height (BH = 12.80±1.30 cm) and body length (BL = 12.80±1.30 cm) was observed in Lavender colour; while the highest beak length (BkL = 4.86±0.69 cm) and neck length (NL = 14.00±0.82 cm) was observed in Chocolate colour. Conclusion: The existing variations in traits among species and individuals are commonly observed situation in genetics across all species of livestock. Despite existing variations, silver phenotype has the highest body weight (BW= 1875.71±243.64 g) and body size (BS = 30.86±1.57 cm). Body weight is a vital economic trait which should be considered for selection and genetic improvement.